2015
DOI: 10.1109/jphot.2015.2395135
|View full text |Cite
|
Sign up to set email alerts
|

An Injection-Locked Weak-Resonant-Cavity Laser Diode for Beyond-Bandwidth Encoded 10-Gb/s OOK Transmission

Abstract: A coherently injection-locked and beyond-bandwidth-modulated weakresonant-cavity laser diode (WRC-FPLD) transmitter packaged by a conventional TO-56 can package for an upstream 10-Gb/s OOK transmission is demonstrated in a DWDM-PON. With specific temperature controlling, the WRC-FPLD is able to maintain its temperature during the process of injection locking. Based on the theoretical analysis of modified rate equations, the injection-locked WRC-FPLD exhibits not only a broadband gain spectrum but also a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Based on a FPLD, Li et al experimentally reported the generation of 19-channel chaotic signals with relative flat power spectra [29]. Compared with conventional FPLDs, weak-resonant-cavity Fabry-Perot laser diodes (WRC-FPLDs) possess broader gain spectra and smaller longitudinal mode interval due to lower front-end reflectivity and longer cavity length [31]- [34]. As a result, much more longitudinal modes can be stimulated in a WRC-FPLD.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a FPLD, Li et al experimentally reported the generation of 19-channel chaotic signals with relative flat power spectra [29]. Compared with conventional FPLDs, weak-resonant-cavity Fabry-Perot laser diodes (WRC-FPLDs) possess broader gain spectra and smaller longitudinal mode interval due to lower front-end reflectivity and longer cavity length [31]- [34]. As a result, much more longitudinal modes can be stimulated in a WRC-FPLD.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing requirement of human being, we want the higher communication speed. As we know, higher speed means that we need less time to communicate the same number of information [3][4][5][6]. The next generation of speed that people want to focus on is about 40Gb per second [7].…”
Section: Introductionmentioning
confidence: 99%
“…For digital optical communication, the digital information is modulated in carrier wave and then it will be transmitted. As we know, the phase modulation is widely applied with better bit error rate (BER) performance [6].…”
Section: Introductionmentioning
confidence: 99%